Experimental study of woven-laminates structures subjected to high-velocity impact. Issue 12 (18th June 2019) - Alonso, Luis; Navarro, Carlos; García-Castillo, Shirley K.
Abstract: This study was designed to evaluate the experimental behavior of monolithic structures consisting of E-glass/polyester woven laminates subjected to high-velocity impact. A number of monolithic laminates with areal densities ranging from 5.94 to 23.76 kg m −2, were studied. The objectives are to study the influence of the composite plate areal density on projectile residual velocity, the minimum energy and velocity of the projectile at the moment of perforation, the energy absorbed by the laminate, the contact time between the plate and the projectile during the impact event and the extension of the damaged surface area on both faces of the laminate.